NARINGINASE IMMOBILIZED ON MODIFIED BANANA PEEL WITH POTENTIAL APPLICATION IN THE CITRUS INDUSTRY (2023)
Banana peel after chemical ant thermal modification was used as an alternative support to immobilize the commercial enzyme naringinase (Penicillum Decumbens); an immobilization yield greater than 70% was observed at pH 7. The morphology of the support was characterized by scanning electron microscopy with elemental analysis, showing the presence of pores and elements such as carbon, oxygen, sulfur, and zinc, while the immobilization of the enzyme was confirmed by infrared spectroscopy. For the free and immobilized enzyme, the KM and Vmax values were 0.0006 mg/mL and 2000 U, and 0.0003 mg/mL and 1666 U, respectively. The temperatures of greatest activity for the free and immobilized enzyme were 70°C and 50°C, respectively, and the optimum pH was 4.5 in both cases. It was found that, after the third use, the catalyst maintained 50% of the enzymatic activity. These results seem to suggest the potential of the synthesized material for its application in the food industry, specifically; in the debittering of citrus juices.